2022
DOI: 10.3390/su14138168
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Factors Affecting Human Reliability in the Mining Process Design Using Fuzzy Delphi and DEMATEL Methods

Abstract: Design errors have always been recognized as one of the main factors affecting safety and health management and sustainable development in surface mines. Unfortunately, scant attention is paid to design errors and the factors causing them. Therefore, based on expert opinions, this study aimed to identify, rank, and investigate cause-and-effect relationships among variables influencing human error in surface mine design in Iran. The study variables were identified by reviewing previous literature on “latent hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…Upon noting some of the limitations of common fuzzy concept-based risk assessment methods (as captured in Table 1), the authors opted for the use of the Fuzzy DEMATEL methodology to assess the causal influences of haul truck accidents in Indian mines. The authors reviewed previous research that utilizes the Fuzzy DEMATEL approach to analyze variables for cause-and-effect relationships in the mining industry in India, Iran, China, and other geographies [26][27][28][29]. The gap in literature that utilizes this methodology to particularly assess the transportation-related risks in Indian mines inspired the present research.…”
Section: Review Of Literature: Risk Analysis In the Mining Industrymentioning
confidence: 99%
“…Upon noting some of the limitations of common fuzzy concept-based risk assessment methods (as captured in Table 1), the authors opted for the use of the Fuzzy DEMATEL methodology to assess the causal influences of haul truck accidents in Indian mines. The authors reviewed previous research that utilizes the Fuzzy DEMATEL approach to analyze variables for cause-and-effect relationships in the mining industry in India, Iran, China, and other geographies [26][27][28][29]. The gap in literature that utilizes this methodology to particularly assess the transportation-related risks in Indian mines inspired the present research.…”
Section: Review Of Literature: Risk Analysis In the Mining Industrymentioning
confidence: 99%
“…This method is based on expert linguistic terminology expressions, which need to be converted from fuzzy linguistic terms to definite values to avoid ambiguity and reach a unified opinion. Fuzzy DEMATEL is a multi-indicator decision-making technique, which has the advantage that the decisionmaking process is based on pairwise comparisons and acceptance relationships, and fuzzy DEMATEL is applied to different areas of research, such as risk assessment and safety management [31,32]. In this paper, to solve the fuzzy problem of expert evaluation in the DEMATEL method, the triangular fuzzy numbers in fuzzy theory are introduced, and the initial direct matrix is fuzzified by applying the semantic evaluation and fuzzy number conversion relation of Li [33].…”
Section: Identification Of Safety Risk Factors For Metro Operationsmentioning
confidence: 99%
“…Expert judgment way has been used in many studies that are concerned with identifying and evaluating the factors influencing human errors during the implementation of inspection and maintenance tasks as [55,59,60]. Several previous studies [61][62][63][64] showed that the accuracy of the analytical value of expert judgments increased with increasing experience and training years of judges. Therefore, we used a group of judges who have more than ten years of experience and training in the field of maintenance, occupational health and safety, and the elicitation was done on an individual basis to avoid biases that may affect the opinions of the expert judgment.…”
Section: B Human Error Modelmentioning
confidence: 99%